2012
DOI: 10.1002/bdd.1782
|View full text |Cite
|
Sign up to set email alerts
|

From preclinical to human – prediction of oral absorption and drug–drug interaction potential using physiologically based pharmacokinetic (PBPK) modeling approach in an industrial setting: a workflow by using case example

Abstract: Purpose: A case example is presented in which the physiologically based modeling approach has been used to model the absorption of a lipophilic BCS Class II compound predominantly metabolized by CYP3A4, and to assess the interplay of absorption related parameters with the drug-drug interaction (DDI) potential. Methods: The PBPK model was built in the rat using Gastroplus W to study the absorption characteristics of the compound. Subsequently relevant model parameters were used to predict the non-linear human P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 25 publications
1
37
0
1
Order By: Relevance
“…This study has identified a significant risk for overestimating DDI liability with Simcyp, largely attributable to uncertainty in CYP3A-mediated intestinal DDIs. This result is consistent with a recent report (Sinha et al, 2012). In the gut, CYP3A represents the principal drug-metabolizing P450 enzyme (Paine et al, 1997(Paine et al, , 2006.…”
Section: Discussionsupporting
confidence: 93%
“…This study has identified a significant risk for overestimating DDI liability with Simcyp, largely attributable to uncertainty in CYP3A-mediated intestinal DDIs. This result is consistent with a recent report (Sinha et al, 2012). In the gut, CYP3A represents the principal drug-metabolizing P450 enzyme (Paine et al, 1997(Paine et al, , 2006.…”
Section: Discussionsupporting
confidence: 93%
“…This is important since drug disposition and DDI mechanisms are generally complex, and models need to be calibrated with both in vitro parameters ("bottom-up") and observed in vivo PK or clinical DDI results ("top-down") Rostami-Hodjegan, 2012;Varma et al, 2012c;Gertz et al, 2013;Varma et al, 2013a;. Although PBPK models are useful to predict DDI risk prior to first-in-human studies, there is a significant level of uncertainty around the human PK and efficacious drug concentration in humans, since these parameters are predicted (Chen et al, 2012;Sinha et al, 2012;Zhao et al, 2012). Therefore, the utility of PBPK models are generally fully realized once human PK have been confirmed and human ADME data obtained to calibrate PBPK models, which could be used to inform decisions on allowable concomitant medications or exclusion criteria during phase II studies and beyond.…”
Section: Predicting Drug-drug Interactionsmentioning
confidence: 99%
“…The application of PBPK modelling for human PK and hence dose prediction has been more widespread in recent years with a number of publications from the Pharmaceutical Industry (7)(8)(9)(10)(11)(12)(13)16,17). In drug discovery and development, PBPK models can be iteratively refined to incorporate additional information on drug disposition as it becomes available from preclinical and clinical studies.…”
Section: Application Of Pbpk Methodologies For Pk and Dose Predictionmentioning
confidence: 99%
“…The integration of physicochemical, in vitro and in vivo data into a PBPK framework to simulate PK profiles of small molecules in humans has become widespread within the Pharmaceutical Industry with numerous groups publishing on their experience with this approach (7)(8)(9)(10)(11)(12)(13)(16)(17)(18)(19). Although PBPK methods have shown utility in predicting human PK a few major challenges remain that need to be addressed to further increase the success of this approach.…”
Section: Challenges and Future Direction Small Molecule Pbpk Modelsmentioning
confidence: 99%
See 1 more Smart Citation